Study of Driven Jaynes-Cummings system - B, Tuguldur; Ts, Gantsog (Scientific transaction of the National University of Mongolia. Physics, 2022)
We investigate a generalized Jaynes-Cummings model with the external field driving the cavity mode. The numerical results for the dynamics of the atom and the cavity field mode are given. Approximated solutions to the Schrodinger equation are supplied, which allow us to predict the kinematics of the Q(a, or*) function in the complex plane.